2021
DOI: 10.3390/su132313369
|View full text |Cite
|
Sign up to set email alerts
|

Application of Entrepreneurial Intention Model in Comparative International Entrepreneurship Research: A Cross-Cultural Study of India and Saudi Arabia

Abstract: The development of entrepreneurial activities helps in realization of multiple goals of sustainable development. This study aims to inspect the applicability of the entrepreneurial intention model (EIM) to explain entrepreneurial intention in different cultural contexts. A survey was conducted using the Entrepreneurial Intention Questionnaire. Based on 535 valid responses received from business students in India (N = 285) and Saudi Arabia (N = 250), the model was analyzed using the partial least square regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 113 publications
(199 reference statements)
0
2
0
Order By: Relevance
“…Gorgievski et al (2018) reported lower EIs among Spanish students than among Dutch, German, and Polish students. Hoda et al (2021) found similar EIs between Indian and Saudi Arabian students. Bouncken et al (2009) observed different EIs between German and Polish students.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Gorgievski et al (2018) reported lower EIs among Spanish students than among Dutch, German, and Polish students. Hoda et al (2021) found similar EIs between Indian and Saudi Arabian students. Bouncken et al (2009) observed different EIs between German and Polish students.…”
Section: Discussionmentioning
confidence: 62%
“…Gorgievski et al (2018) found that, out of the TPB variables, ATE had the strongest relationship with EIs. Hoda et al (2021) also concluded that attitude and behavioural control significantly impact intentions among Indian and Saudi Arabian students. Several studies have confirmed the positive and significant effect of attitude and behavioural control (Liñán, Chen, 2009;Koe, 2016;Leiva et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As for the role of perceived behavior control, according to [106], it has a significant influence on entrepreneurship. In addition, [107] stated that the level of influence of attitudes, subjective norms, and perceived behavioral control on the model of entrepreneurial activity in each country would, of course, be different. This is influenced by the culture and social life that is formed in each country.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study by [112] stated that during the pandemic, young entrepreneurs were able to adopt digital entrepreneurship in developing their businesses. Moreover, [107] states that the level of influence of attitudes, subjective norms, and perceptions of behavioral control on models of entrepreneurial activity in each country will certainly be different. This is influenced by the culture and social life that is formed in each country.…”
Section: Discussionmentioning
confidence: 99%